Time of initiation of breastfeeding in various modes of delivery and to observe the effect of low birth weight and period of gestation on initiation of breastfeeding - Badaya, Navneet; Jain, Sanjiv; Kumar, Nayan (International Journal of Contemporary Pediatrics, 2018)
Background: There are certain factors influencing early initiation of breastfeeding, most of them can be corrected by paying little attention and by making certain strategies for the other factors. Study the difference between the time of initiation of breastfeeding in vaginally delivered and caesarean born deliveries, evaluate the effect of low birth weight and period of gestation on initiation of breastfeeding and to promote and encourage the breastfeeding. Methods: This observational prospective study was conducted on 500 newborns delivered at Department of RMC, Ajmer and outborn section of Department of Pediatrics, JLN MC, Ajmer. The study group was divided two groups, group- I 250 newborn delivered vaginally and group-II 250 newborn delivered by caesarean section. Results: Among birth weight >2500gm, in 146 (41.83%) cases breastfeeding was started in 0-1 hr, in 172 (49.28%) cases in 1-4 hours. Thus 91.11% initiated breastfeeding in first 8 hours (p value <0.00002), showing early initiation of breastfeeding in >2500g newborn. Among term babies, out of 398 (79.6%) babies with period of gestation 37-41 weeks, in 162 (40.70%) cases breastfeeding was initiated in 0-1 hour, in 185 (46.48%) cases in 1-4hr (p value <0.0391). Thus, 347(81.18%) initiated breastfeeding in first 8 hours. Conclusions: Term gestation is positively associated while low birth weight and prematurity of baby has negative impact on early initiation of breastfeeding.